Five have a mystery to solve - Blyton, Enid. (b, 2004)
The Famous Five investigate the creepy stories surrounding Whispering Island and discover they are not alone.
Keywords: Famous Five (Fictitious characters) -- Juvenile fiction; Famous Five (Fictitious characters) -- Fiction; Adventure & thriller